Non-linear behavior of mass concrete in three dimensional problems using a smeared crack approach. - Mirzabozorg, H. (Earthquake engineering & structural dynamics.)
A smeared crack approach has been proposed to model the static and dynamic behavior of mass concrete in three-dimensional space. The proposed model simulates the tensile fracture on the mass concrete and contains pre-softening behavior, softening initiation, fracture energy conservation and strain rate effects under dynamic loads. The validity of the proposed model has been checked using the available experimental results under static and dynamic loads. The direct and indirect displacement control algorithms have been employed under incremental increasing static loads. It was found that the proposed model gives excellent results and crack profiles when compared with the available data under static loads. The Koyna Dam in India hs been used to verify the dynamic behavior of the proposed model. It was found that the resulting crack profiles were in good agreement with the available experimental results. Finally, the Morrow Point Dam was analyzed, including the dam-reservoir interaction effects, to consider its non-linear seismic behavior. It was found that the resulting crack profiles were in good agreement with the contour of maximum principal stresses and no numerical instability occured during the analysis.